Evaluation of Serum Cortisol Level in Chronic Superficial Dermatophytosis - Varsha Dubey; Madhur Kant Rastogi; Nitin Mishra; Pratik Gahalaut; Amar Singh; Aaruj Dudea (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: The epidemic-like scenario of superficial fungal infections in India has been complicated by the rampant use of systemic and topical potent steroids. In this study, we hypothesize that the unjudicial use of topical corticosteroids can cause Hypothalamic pituitary axis suppression in chronic dermatophytosis patients.